2021
DOI: 10.21203/rs.3.rs-36911/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bilateral Posterior Quadratus Lumborum Block for Pain Relief after Cesarean Delivery: A Randomized Controlled Trial

Abstract: Background: Achieving optimal analgesia with few side effects is the goal of pain management after cesarean delivery. Intrathecal (IT) morphine is the current standard but ultrasound-guided quadratus lumborum block (QLB) may offer superior pain control with fewer side effects. This study compared the pain-free period after cesarean delivery among parturients who received spinal block with IT morphine, with IT morphine and bilateral QLB, or only bilateral QLB.Methods: Parturients having elective cesarean deli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…23 Hence, morphine is recommended, rather than short-acting opioids, to be added to spinal bupivacaine for providing postoperative analgesia after Cesarean section. Although, the quadratus lumborum block might be a technique to replace, and avoid ITM-induced side effects in Cesarean delivery, evidence showed that it did not have additive analgesic effects when combined with ITM; additionally, it was inferior to ITM when used alone in patients undergoing Cesarean section [24][25] Although, we could not eliminate intrathecal morphine-induced side effects to zero, we could reduce them as much as possible by reducing the dose of ITM. However, this will reduce the analgesic effects as well.…”
Section: Discussionmentioning
confidence: 97%
“…However, a number of studies compared QLB with intrathecal morphine and demonstrated that the analgesia provided by intrathecal morphine is superior to QLB (15,20,21) . Moreover, QLB provides no benefit compared to sham procedure when intrathecal morphine is used as part of postoperative multimodal analgesia (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…The original lateral approach (QLB-I) (23) is now not used after CS. (12) Most of the current studies have utilized the posterior approach (QLB-II) (12,13,(15)(16)(17)(19)(20)(21)(22) , however, other studies have successfully utilized the transmuscular approach (QLB-III) (14,18) .…”
Section: Discussionmentioning
confidence: 99%